3D printing technology: The new era for food customization and elaboration. (May 2018) - Dankar, Iman; Haddarah, Amira; Omar, Fawaz E.L.; Sepulcre, Francesc; Pujolà, Montserrat
Abstract: Background: Digitalizing food using 3-Dimensional (3D) printing is an incipient sector that has a great potential of producing customized food with complex geometries, tailored texture and nutritional content. Yet, its application is still limited and the process utility is under the investigation of many researchers. Scope and approach: The main objective of this review was to analyze and compare published articles pertaining 3D food printing to ensure how to reach compatibility between the huge varieties of food ingredients and their corresponding best printing parameters. Different from previously published reviews in the same journal by Lipton et al. (2015) and Liu et al. (2017), this review focuses in depth on optimizing extrusion based food printing which supports the widest array of food and maintains numerous shapes and textures. The benefits and limitations of 3D food printing were critically reviewed from a different perspective while providing ample mechanisms to overcome those barriers. Key findings and conclusions: Four main obstacles hamper the printing process: ordinance and guidelines, food shelf life, ingredients restrictions and post processing. Unity and integrity between material properties and process parameters is the key for a best end product. For each group, specific criteria should be monitored: rheological, textural, physiochemical and sensorial properties of the material its self in accordance with the process parameters of nozzle diameter, nozzle height, printing speeds and temperature of printing. It is hoped that this paper will unlock further research on investigating a wider range of food printing ingredients and their influence on customer acceptability. Highlights: 3D Printing different domains of approaches. Benefits of 3D food printing: sectors of applications. Overview of 3D food printing technologies and applicable companies. Obstacles that might be faced during 3D food printing. Process parameters and material properties compatibility for 3D food printing.